Corporate social responsibility disclosures as an indicator of social performance and its relation with financial performance - Yılmaz, İlker (My University, 2011)
Geleneksel olarak, şirketlerin nihai amacının kar etmek olduğu, kendilerini sorumlu hissettikleri tek grubun hissedarlar olduğu ve finansal yönetimin amacının hissedar değerini maksimize etmek olduğu bilinir. Bu amaçların büyük önemi olsa da, bunlar yegane kaygı değil ve olmamalıdır. Son yıllarda, şirketlerin hissedarların yanında daha geniş bir pay sahipleri grubu için var olduğu ve onlara karşı sorumlulukları olduğu yaklaşımı hem akademik çevrede, hem de iş hayatında giderek önem kazanmaktadır. Şirketler, faaliyetlerini sosyal ve çevresel sonuçlarını da göz önünde bulundurarak yerine getirmeli, “sürdürülebilirlik” kavramını faaliyetlerine entegre etmelidir. Sürdürülebilir kalkınma ve büyüme için şirketlere de önemli görevler düşmektedir. Tüm bu sorumluluklar, “kurumsal sosyal sorumluluk” (KSS) olarak adlandırılmaktadır. Literatürde, KSS faaliyetlerinin şirketlere faydalı olup olmadığı; şirketin finansal performansı ile ilişkisi olup olmadığı ve ilişkinin yönü ile ilgili araştırmalar yapılmıştır. Bu çalışmada, şirketlerin sosyal performanslarının finansal performans ve pozisyonları üzerinde veya finansal performans ve pozisyonun sosyal performans üzerinde bir etkisinin olup olmadığı araştırılmıştır. Avrupa ve ABD’nin aksine, Türkiye’de şirketlere yönelik KSS derecelendirmesi olmadığı için, faaliyet raporları ile içerik analizi yapılarak, KSS raporlaması standartları ve çeşitli derecelendirme kuruluşlarının kriterleri baz alınarak hazırladığımz ölçek üzerinden puanlama yapılmıştır. Bu puanlar ve finansal göstergeler kullanılarak, panel veri analizi yapılmıştır. Toplam Varlıklar ve Net Faaliyet Karı göstergeleri anlamlı sonuçlar verirken, diğer finansal göstergeler anlamsız sonuçlar verdi. KSS faaliyetlerinin raporlaması çok düşük seviyelerde bulunmaktadır. Şirketlerin KSS ve sürdürülebilirlik bilincinin artması büyük önem taşımaktadır, şirketler bu alanlarda daha aktif roller üstlenmelidir.

Traditionally, companies are known as that their ultimate objective is to make profit, shareholders are the only party toward which the company has responsibilities and the ulimate objective of financial management is to maximize shareholder value. Although those objectives have a great importance, they are not, and must not be, the only concern. In recent decades, it is gaining more and more dominance in both academic and business life that the company exists for and has responsibilities toward a wider group of stakeholders and it must have some objectives other than profitability. The company must perform business operations by taking into account the social, environmental consequences. It must integrate into its operations the idea of sustainability. In order to achieve sustainable development and growth, the companies must assume more duties, which is called the term “corporate social responsibility (CSR).” In the literature, it is questioned whether CSR activities benefit the company or not; whether there is any relationship exists between CSR activities and the company’s financial performance and the direction of the relationship. In this study, we aimed to explore that whether there is any effect corporate social performance (CSP) on financial performance and position and vice versa. The data source for CSP is the annual reports. In the absence of CSP ratings in Turkey despite EU and USA, we performed content analysis through annual reports and derived a social score composed of the items included in disclosure guidelines and some criteria used in CSR ratings. We also used several financial indicators which are of two types; financial position and financial performance indicators. In order to explore the relationship between CSP and financial indicators, we run panel data regressions. We found significant results for some of the indicators, for instance, Total Assets and Net Operating Profit; where some of the indicators gave insignificant results. The reporting of CSR activities is in very low levels. The conscious toward corporate social responsibility and sustainability must be promoted and the companies must assume more active roles. The reporting of those activities is also important. The companies must pay more attention to publish CSR and sustainability activities.
Keywords: Finansal Performans; Kurumsal Sosyal Sorumluluk; Muhasebe